Formação inicial de professores de Educação Física para atuação com alunos com necessidades educacionais especiais - Almeida, Luiz Fernando Garcia de (2017)
The present study aims to investigate if the disciplines that compose the curriculum of the Physical Education graduation course from State University of the Paraná West contribute to the initial formation of the future teachers regarding to the pedagogical work with students with special educational needs inserted in regular education. In order to attend this objective, we have opted for an exploratory research characterized as a case study. There was also a need for a study of the Political Pedagogical Project (PPP) to gather the information regarding to the contextualization of the course and a study of the teaching plans with the intention of verifying if they approach contents or themes focused on the pedagogical work with these students. As a theoretical reference, we are based on Historical-Cultural Psychology from Vigotski. The data collection initially occurred through the application of a questionnaire with the 19 teachers who composed the faculty of the course in the year 2016. Then, a structured interview was conducted with only nine teachers who affirmed in the questionnaire they contemplate contents involving the process of schooling of students with special educational needs. The data were analyzed by the perspective of the content analysis technique from Bardin (2011). In this way, from the total of 36 disciplines, according to the participants answers, we find that16 disciplines approaches its contents about this subject and another two are specific in Special Education. In 10 of these 16 disciplines, the participants mentioned that, in their pedagogical practices, they contemplate these contents in an articulated way to the others worked during the year; in another six disciplines, they answered that, besides the contents of the teaching plan, they still include specific contents on this theme. In addition to it, all interviewees were unanimous in affirming that their disciplines really contribute to the initial formation of academics to act in the Special Education, as well as, we can say that the interaction between contents or themes from the disciplines that compose the curriculum of the course reaffirms the importance of the articulation between them, so that this interdisciplinary interaction presents itself as a possibility that significantly contributes to the initial formation of the future teachers regarding to the pedagogical work with students with special educational needs inserted in regular education.